(untitled) (Journal of Current and Advance Medical Research, 2021)
Background: Seizure is a common neurological disorder in the pediatric age group. Objective: Neonates with seizure have decreased in serum calcium, magnesium, sodium, potassium, and glucose if compared to neonates without seizure. Methodology: This comparative cross-sectional study was carried out in the Department of Biochemistry at Mymensingh Medical Collage, Mymensingh, Bangladesh in cooperation with the Department of Pediatric of Mymensingh Medical Collage & Hospital, Mymensingh, Bangladesh from July 2005 to June 2006. Neonates were included in the study. Subjects were divided into two groups designated as group I as control group and group II cases. From each subject at least 2 ml of blood were collected from femoral vein and was collected serum for biochemical analysis. Result: A total of 60 neonates were included in the study. Subjects were divided into two groups-group-I control- (n=20) and group II cases-(n=40). The concentration of serum calcium, magnesium, sodium, potassium, and glucose yielded 7.33 ±0.79, 5.79 ±1.10; 2.18 ± 0.23,1.61 ± 0.25; 134.82 ±3.03, 133.68±8.57; 4.80 ±0.56,5.89 ±2.02; 66.33 ± 8.23, 62.25± 7.96 in group I and group II respectively. Conclusion: Significant decreases of serum calcium, magnesium and significant increase of serum potassium in neonates with seizure are found in this study. The change in serum sodium and glucose are not significant. Journal of Current and Advance Medical Research, January 2021;8(1):25-29